Validating the hybrid ERTMS/ETCS level 3 concept with electrum - Cunha, Alcino (2018)
This paper reports on the development of a formal model for the Hybrid ERTMS/ETCS Level 3 concept in Electrum, a lightweight formal specification language that extends Alloy with mutable relations and temporal logic operators. We show how Electrum and its Analyzer can be used to perform scenario exploration to validate this model, namely to check that all the example operational scenarios described in the reference document are admissible, and to reason about expected safety properties, which can be easily specified and model checked for arbitrary track configurations. The Analyzer depicts scenarios (and counter-examples) in a graphical notation that is logic-agnostic, making them understandable for stakeholders without expertise in formal specification.